Review Pengenaan Bea Masuk Anti Dumping Produk A4 Copy Paper Oleh Australia - Maheralia, Resti; faradila, fitria (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2025)
In 2022, Australia decided to extend the anti-dumping duty on A4 copy paper which has been imposed to, inter alia, Indonesia with a reviewed duty by 59.7% and the implementation will be in force until 2027. This article aims to review of such measure imposed by Australia to Indonesia and how it affects Indonesia’s export. The research utilizes descriptive analysis to depict the anti-dumping case study. The analysis was obtained from several literatures, for example Australian Anti-Dumping Commission report and related journals. To analyze the problems, the Global Trade Analysis Project (GTAP) simulation was employed and analyzed quantitatively. This study concludes that the impact of the aforementioned duty on A4 paper originating in Indonesia is relatively low to Indonesia's macroeconomic conditions. However, the impact on Indonesia’s paper industry is quite significant because all performance indicators decrease. After the imposition of the measure, the Indonesian paper industry has also not been able to diverse its market directly to its domestic market. The market access barrier to Australia and a decline in its domestic sales caused the Indonesian paper industry's production, investment, and exports to decline. As a consequence, the Indonesian paper industry will tend to reduce the absorption of its workforce. This study is expected to elaborate and evaluate the extent to which the countries subject to the imposition of the anti-dumping duty are affected when evaluated by certain economic performance. Government of Indonesia is expected to actively defences Indonesia’s position which is alleged dumping in trading partner countries.